The Effectiveness of Quantum Learning Method to Students’ English Learning Achievement at SMK N 9 Padang - Zia Syukria (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This research aimed to find out the effectiveness of Quantum Learning Method to students’ English learning achievement. This research was pre-experimental design in the form of one group Pretest- Posttest. It was conducted at SMK N 9 Padang. The sample of this research was class X Hotel Acomodation 3 with total number of sample was 27. The instrumentation used as a data collection was test. The findings showed the effectiveness of using quantum learning methods which can be seen from the value of learning achievement. The findings of this research; quantum learning method is quite effective to improve students' English learning achievement on the material "announcement", this is indicated by the value of  5.17 was bigger than the value of  2.060 with level of significance 0.05.